Transpiration Rate of White Clover (Trifolium repens L.) Cultivars in Drying Soil - Egan, Lucy; Hofmann, Rainer; Nichols, Shirley; Hadipurnomo, Jonathan; Hoyos-Villegas, Valerio (Frontiers in Plant Science, 2021)
Determining the performance of white clover cultivars under drought conditions is critical in dry climates. However, comparing the differences in cultivar performance requires equivalent soil water content for all plants, to reduce the water deficit threshold eliciting stomatal closure . In this study, the objective was to compare the rate of stomatal closure in eighty white clover cultivars in response to soil drying. Two glasshouse experiments were conducted, and the daily transpiration rate was measured by weighing each pot. The transpiration rate of the drought-stressed plants were normalized against the control plants to minimize effects from transpiration fluctuations and was recorded as the normalized transpiration rate (NTR). The daily soil water content was expressed as the fraction of transpirable soil water (FTSW). The FTSW threshold (FTSWc) was estimated after which the NTR decreases linearly. The FTSWc marks the critical point where the stomata start to close, and transpiration decreases linearly. The significant difference (p<0.05) between the ten cultivars with the highest and lowest FTSWc demonstrates the cultivars would perform better in short- or long-term droughts.